2016
DOI: 10.18632/oncotarget.13973
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-derived exosomes as a signature of pancreatic cancer - liquid biopsies as indicators of tumour progression

Abstract: Pancreatic cancer is the fourth most common cause of death due to cancer in the world. It is known to have a poor prognosis, mostly because early stages of the disease are generally asymptomatic. Progress in pancreatic cancer research has been slow, leaving several fundamental questions pertaining to diagnosis and treatment unanswered. Recent studies highlight the putative utility of tissue-specific vesicles (i.e. extracellular vesicles) in the diagnosis of disease onset and treatment monitoring in pancreatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 74 publications
(93 reference statements)
0
54
0
Order By: Relevance
“…Indeed, this may also be cost-effective, as the isolation and use of exosomal biomarkers from patients would certainly be cheaper, less invasive, and potentially more sensitive and specific than many of the current clinical diagnostic tests. 46 Interestingly, the glypicans family is an attractive candidate and several previous studies reported that exosome-associated GPC1 was a highly specific and sensitive biomarker for early detection of pancreatic cancer. 47,48 Our results indicate that GPC4 might be considered as an alternative diagnostic and prognostic biomarker in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this may also be cost-effective, as the isolation and use of exosomal biomarkers from patients would certainly be cheaper, less invasive, and potentially more sensitive and specific than many of the current clinical diagnostic tests. 46 Interestingly, the glypicans family is an attractive candidate and several previous studies reported that exosome-associated GPC1 was a highly specific and sensitive biomarker for early detection of pancreatic cancer. 47,48 Our results indicate that GPC4 might be considered as an alternative diagnostic and prognostic biomarker in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, their invasiveness, along with tumor sampling brings about challenges with studying tumor heterogeneity and evolution, making it an unlikely process for regular monitoring (Vaidyanathan, Soon et al 2019). vesicles / mL in blood, (Keller, Ridinger et al 2011, Lee, Fraser et al 2018, making EVs highly abundant and easily available biomarkers (Nuzhat, Kinhal et al 2017, Rajagopal and Harikumar 2018, Rodrigues, Fan et al 2018, van Niel, D'Angelo et al 2018. Critical information is stored in the molecular profile of the exosomal cargo and surface expression due to their endocytotic biogenesis from parent tumor cells making them favorable for studying tumor microenvironment (Kalluri 2016).…”
Section: The Emergency Of Liquid Biopsy In Cancer Diagnosticsmentioning
confidence: 99%
“…Currently, there are no reliable markers that can accurately diagnose, classify and predict the biological behavior of pancreatic tumors. Therefore, it is imperative to focus on identifying and developing biomarkers, with high specificity and sensitivity that can help detect initial lesions in the early stages of pancreatic cancer (Herreros-Villanueva and Bujanda 2016, Nuzhat, Kinhal et al 2017) There are potential serum biomarkers for diagnosis, disease progression and monitoring of therapy (Hidalgo 2010). Carbohydrate antigen, CA19-9 is currently the most extensively studied biomarker and the only one approved by the FDA with demonstrated clinical usefulness (Goonetilleke and Siriwardena 2007).…”
Section: Determining the Blocking Buffermentioning
confidence: 99%
See 1 more Smart Citation
“…The miRNA expression patterns have been shown to be highly tissue-specific, providing great potential as a tumorspecific biomarker. In addition, miRNA dysregulation has been reported as a feature of pancreatic cancer progression, and the transfer of EV miRNAs has been shown to cause biological changes in recipient cells (30,31). To profile the miRNA cargo in EVs at various stages of pancreatic cancer, we isolated EVs using pan-exosome markers (CD9, CD81) from 500 mL of mouse plasma using the KPCY model (n ¼ 2 healthy, n ¼ 6 PanIN, and n ¼ 5 PDAC; ref.…”
Section: Ev Mirna Biomarker Sequencingmentioning
confidence: 99%